Effect of temperature on viability of human hydatid cyst & study the volume of hydatid cyst (Baghdad Science Journal, 2025)
The hydatid materials were collected and studied, so they were contained 50 fertile human hydatid cases {33 (66%) females and 17 (34%) males}. They were collected from Al-Ramadi General Hospital during the period from December, 2003 to July, 2004 .Cysts were observed in 40 (80%) from the liver, 5 (10%) from the lungs, 3 (6%) from the kidney and 2 (4%) cysts from urinary bladder. The specimens were taken from patients of different ages. The in vitro viability of protoscoleces was assessed on the basis of flame cell activity and eosein exclusion, which were considered as criteria to determine the death or viability of protoscoleces. In addition to this movement (flame cell activity), another motility like constriction – relaxation (invagination - evagination) in the protoscoleces was also noticed. Both types of movement were examined under light microscope. The motility of protoscoleces examined under effect of three different temperature degrees 25?C, 37?C, and 40?C was within 15 minutes. It showed steadily increase with rising temperature. Flame cell activity increased as high as 70.01% at 40?C, while the motility with constriction -relaxation movement increased as 100.0% at 40?C. The volumes of hydatid cysts were also studied, so they were measured. Therefore, the volumes of human hydatid cysts were the highest in the lung and this is may be due to the spongy texture of the lung tissues. There is relationship between the volumes of Hydatid cysts and the viability was recorded.